2015
DOI: 10.1007/s10457-015-9836-4
|View full text |Cite
|
Sign up to set email alerts
|

Carbon storage in livestock systems with and without live fences of Gliricidia sepium in the humid tropics of Mexico

Abstract: Agroforestry systems (AFS) play a major role in the sequestration of carbon (C). The objectives of this study were to quantify the organic C stocks in the above-and below-ground tree biomass and in the soil in a cattle-farming system with live fences (CFSLF) of Gliricidia sepium and to compare the levels with those of a cattle-farming system based on a grass monoculture (CFSGM). The methodology included a forest inventory in nine randomly assigned plots and the destructive sampling of G. sepium 32 trees, measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 38 publications
0
8
1
3
Order By: Relevance
“…Kunth ex Walp) and the values of 15.21 Mg C ha −1 reported by Nair et al (2009) in a combination of species. In the case of the below‐ground biomass, our results show that the tree root biomass contributes 14.20% of the total tree biomass of the system, which is lower than the values of Villanueva‐López et al (2015) who reported a below‐ground biomass of 21% in SPS with live fences of G . sepium .…”
Section: Discussioncontrasting
confidence: 93%
“…Kunth ex Walp) and the values of 15.21 Mg C ha −1 reported by Nair et al (2009) in a combination of species. In the case of the below‐ground biomass, our results show that the tree root biomass contributes 14.20% of the total tree biomass of the system, which is lower than the values of Villanueva‐López et al (2015) who reported a below‐ground biomass of 21% in SPS with live fences of G . sepium .…”
Section: Discussioncontrasting
confidence: 93%
“…Walp. compared to 26 g kg −1 at the distance of 6-9 m from the live fence in tropical pastureland of Brachiaria decumbens Stapf [73]. The diurnal and seasonal variation in soil temperature, soil moisture, and soil respiration were lower in a silvopastoral system with live fences of G. sepium compared to pasture monoculture in those sites [19].…”
Section: Management Recommendations For Carbon Stock Enhancement In Tmentioning
confidence: 88%
“…Since the extension of grassland is increasing, proper management is necessary to mitigate SOC losses [71,72]. Management practices like the establishment of agroforestry systems that combine grasses with shrubs and trees increase SOC stocks, in addition to providing potential increases in the nutritional value of animal forage and other opportunities to provide resources such as human food, wood, and fuelwood [17,26,73]. There are studies demonstrating that agroforestry practices can significantly increase biomass and soil carbon storage in livestock systems [28,74].…”
Section: Management Recommendations For Carbon Stock Enhancement In Tmentioning
confidence: 99%
“…De este modo, al mismo tiempo que mejoran las prácticas de producción ganadera, mitigan los efectos del cambio climático, contribuyen a la conservación de la biodiversidad y reducen la deforestación o la degradación de los bosques, reduciendo emisiones de carbono y aumentando la captura de este gas en la parte forestal (Amézquita, Ibrahim, Llanderal, Buurman y Amézquita, 2004). En conjunto, estas ecotecnologías conforman estrategias versátiles para la mitigación y la adaptación al cambio climático global en México, mejorando la resiliencia de los sistemas productivos (Ferguson et al, 2013;Jiménez-Ferrer, Aguilar-Argüello y Soto-Pinto, 2008;Nahed-Toral et al, 2013;Villanueva, Martínez, Casanova, Ramírez y Montañez, 2015).…”
Section: Innovación Ecotecnológica En Sistemas Pecuariosunclassified